Association of BMI with general health, working capacity recovered, and post‐acute sequelae of COVID‐19. Issue 1 (16th November 2022) - Peter, Raphael S.; Nieters, Alexandra; Brockmann, Stefan O.; Göpel, Siri; Kindle, Gerhard; Merle, Uta; Steinacker, Jürgen M.; Kern, Winfried V.; Rothenbacher, Dietrich
Abstract: Objective: The aim of this study was to determine the risk of post‐acute sequelae of COVID‐19 associated with the continuous spectrum of BMI. Methods: Epidemiology of Long COVID (EPILOC) is a population‐based study conducted in Baden‐Württemberg (Germany), including subjects aged 18 to 65 years who tested positive for SARS‐CoV‐2 between October 2020 and April 2021. Eligible subjects answered a standardized questionnaire, including sociodemographic characteristics, lifestyle factors, and the presence of specific symptoms. Participants assessed their current general health recovery and working capacity compared with the pre‐infection situation and provided their body height and weight. Generalized additive models were used to assess the association of BMI with general health recovered, working capacity recovered, and prevalence of fatigue, cognitive impairment, and chest symptoms. Results: The analyses included 11, 296 individuals (41% male), with a mean age of 44.0 (SD 13.7) years. Best general health recovery was observed at BMI of 22.1 (95% CI: 21.0‐27.0) kg/m 2 in men and BMI of 21.6 (95% CI: 20.3‐23.1) kg/m 2 in women. In addition, we found that increasing BMI was consistently associated with post‐COVID fatigue, neurocognitive impairment, and chest symptoms. Conclusions: High BMI contributes to impaired recovery after SARS‐CoV‐2 infection; however, a low BMI is associated with impaired recovery as well.